Endocrine Disruptor Degradation by UV/Chlorine and the Impact of Their Removal on Estrogenic Activity and Toxicity. (8th May 2019) - Saggioro, Enrico M.; Chaves, Fernanda P.; Felix, Louise C.; Gomes, Giselle; Bila, Daniele M.
Abstract : Recently, chlorination disinfection technology applying ultraviolet radiation (Cl/UV) has received attention as an advanced oxidative process (AOP) for the generation of highly oxidant species. Many studies have evaluated its effects on pathogen inactivation, contaminant removal, and formation of disinfection by-products (DBPs). However, the degradation of three endocrine disruptor chemicals (EDCs), 17 β -estradiol (E2), 17 α -ethinylestradiol (EE2), and bisphenol-A (BPA), associated with simultaneous disinfection and estrogenic activity and ecotoxicity assessments has not yet been reported. Compound degradation increased with increasing chlorine concentrations (2 mg·L -1 chlorine), with pseudo-first-order kinetics1.86 × 10 − 2 s -1, 3.06 × 10 − 2 s -1, and3.09 × 10 − 2 s -1 for BPA, E2, and EE2, respectively. The degradation kinetics in a WWTP effluent significantly decreased to4.94 × 10 − 2 min -1, 4.75 × 10 − 2 min -1, and4.84 × 10 − 2 min -1, for BPA, E2, and EE2, respectively. However, 45% TOC removal and disinfection of E. coli and total coliform bacteria (TCB) were observed in 10 min of treatment. The yeast estrogen screen (YES) revealed that the treatment did not form by-products with estrogenic activity, demonstrating cleavage or mineralization in the phenolic group, common to all assessed compounds. High cell growth inhibition and mortality for Raphidocelis subcapitata and Ceriodaphnia dubia, respectively, were observed during the photodegradation process. Thus, the formed DBPs may be responsible for the observed toxicity and should be taken into account in WWTP treatments in order to monitor the formation of chlorinated by-products.